2010
DOI: 10.1017/s1751731109990620
|View full text |Cite
|
Sign up to set email alerts
|

Methane mitigation in ruminants: from microbe to the farm scale

Abstract: Decreasing enteric methane (CH 4 ) emissions from ruminants without altering animal production is desirable both as a strategy to reduce global greenhouse gas (GHG) emissions and as a means of improving feed conversion efficiency. The aim of this paper is to provide an update on a selection of proved and potential strategies to mitigate enteric CH 4 production by ruminants. Various biotechnologies are currently being explored with mixed results. Approaches to control methanogens through vaccination or the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
657
6
32

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 747 publications
(751 citation statements)
references
References 145 publications
13
657
6
32
Order By: Relevance
“…The ED computed for equation N was lower than obtained by Ellis et al (2009) (76.4% v. 95.8%, respectively). Fat content of diets, which is associated with lower CH 4 production (Martin et al, 2009), was not considered by any of the best-fit equations but may be indirectly considered by equations that include GEI, when GE content is measured directly rather than assumed to be constant.…”
Section: Discussionmentioning
confidence: 99%
“…The ED computed for equation N was lower than obtained by Ellis et al (2009) (76.4% v. 95.8%, respectively). Fat content of diets, which is associated with lower CH 4 production (Martin et al, 2009), was not considered by any of the best-fit equations but may be indirectly considered by equations that include GEI, when GE content is measured directly rather than assumed to be constant.…”
Section: Discussionmentioning
confidence: 99%
“…A range of different strategies are being investigated to reduce methane emissions from farmed ruminants (reviewed by Martin et al, 2010;Buddle et al, 2011;Clark, 2013). Vaccination of ruminants against rumen methanogens has the potential to reduce methane emissions by decreasing the number or activity of methanogens in the rumen.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the concentration of dietary lipid has been shown to reduce CH 4 emissions from ruminants (Martin et al, 2010;Grainger and Beauchemin, 2011;Patra, 2013). This is achieved through various mechanisms: fatty acids are not fermented in the rumen and therefore increasing dietary lipid concentration reduces the proportion of feed which is fermentable within the rumen; lipids can also reduce CH 4 production by coating fibre particles, reducing their digestibility, and by reducing the numbers and activity of the rumen methanogens and protozoa responsible for methanogenesis (Johnson and Johnson, 1995;Patra, 2013).…”
mentioning
confidence: 99%
“…Although increased concentrations of dietary lipid has been shown to reduce CH 4 from ruminants (Martin et al, 2010;Grainger and Beauchemin, 2011;Patra, 2013), at high concentrations in the diet lipid can negatively affect DMI and productivity (Brask et al, 2013). Based on a meta-analysis, Patra (2013) demonstrated that dietary lipid concentrations in excess of 6% cause problems with productivity.…”
mentioning
confidence: 99%